Interfacial characterization of nickel–yttria-stabilized zirconia cermet anode/interconnect joints with Ag–Pd–Ga active filler for use in solid-oxide fuel cells. (21st January 2015) - Chao, Chih-Long; Chu, Chun-Lin; Fuh, Yiin-Kuen; Hsu, Ray-Quen; Lee, Shyong; Cheng, Yung-Neng
Abstract: Nickel–yttria-stabilized zirconia cermet anode (Ni–YSZ)/interconnect joints with silver–palladium–gallium (Ag–9Pd–9Ga) active fillers are prepared by vacuum brazing. The joint structure and microstructure are analyzed by X-ray diffraction (XRD) and scanning electron microscopy coupled with energy dispersive spectroscopy (SEM/EDS), and by using an electron probe microanalyzer (EPMA). SEM observations of the joint show no cracks near the interface, confirming the compatibility of the Ag–9Pd–9Ga filler with a different anode and interconnect. The XRD pattern of the joint specimens oxidized at 800 °C for 250 h shows Cr2 O3 and (Mn, Cr)3 O4 surface layers. EPMA analysis of the cell/Ag–9Pd–9Ga/alloys joint at the cross section shows Cr, O, Fe, Zr, Ni, Ag, Pd, Ga, Y, and Mn. Overall, the results indicate that the bonding between metal and cermet is well established and the interface is smooth. By correlating the XRD and EPMA analysis results, we also analyzed the possible stages during joint oxidation. The joint strength was evaluated at 25 and 800 °C under shear and tensile loading conditions, respectively, and the brazed Ag–9Pd–9Ga sealant compared favorably with the commercially available glass-ceramic GC-9 counterpart. Highlights: A technique is developed to measure strength of Ni–YSZ/Ag–Pd–Ga/metal interconnect joint. 800 °C for 500 h oxidation do not result in the formation of cracks at the interface between Ag–Pd–Ga/metal interconnect joint. Ag–Pd–Ga seal on metal interconnects than those for the glass-ceramic counterpart GC-9.